Phase Evolution and Microstructural Studies in CaZrTi2O7–Nd2Ti2O7 System. Issue 2 (7th December 2013) - Jafar, Mohsin; Sengupta, Pranesh; Achary, Srungarpu N.; Tyagi, Avesh K.
Abstract : A series of compositions with general stoichiometry Ca1− x Zr1− x Nd2 x Ti2 O7 has been prepared by high‐temperature solid‐state reaction of component oxides and characterized by powder X‐ray diffraction and electron probe for microanalyses (EPMA). The phase fields in CaZrTi2 O7 –Nd2 Ti2 O7 system and distribution of ions in different phases have been determined. Four different phase fields, namely monoclinic zirconolite, cubic perovskite, cubic pyrochlore, and monoclinic Nd2 Ti2 O7 structure types are observed in this system. The 4M‐polytype of zirconolite structure is stabilized by substitution of Nd 3+ ion. The addition of Nd 3+ ions form a cubic perovskite structure‐type phase and thus observed in all the compositions with 0.05 ≤  x  ≤ 0.80. Cubic pyrochlore structure‐type phase is observed as a coexisting phase in the nominal composition with 0.20 ≤  x  ≤ 0.90. Only a subtle amounts of Ca 2+ and Zr 4+ are incorporated into the perovskite‐type Nd2 Ti2 O7 structure. EPMA analyses on different coexisting phases revealed that the pyrochlore and perovskite phases have Nd 3+ ‐rich compositions.